The Effectiveness of Social Play Therapy To Improve Social Skills And Abilities Of Children With Autism - MA Muazar Habibi (UNIB Press, 2023)
In the last three years, many children in West Nusa Tenggara, especially in West Lombok Regency in Indonesia, have experienced a developmental disorder called autism. This can be seen from the rise in public attention to include this category of children in schools that hold inclusive classes, such as in Early Childhood Education-Elementary School Lenterahati Islamic Boarding School. The increase in autism is also evidenced by the emergence of various therapy centres for children with special needs, as well as the increasing number of participants enrolled and undergoing therapy. The initial survey results showed seven therapy centres and schools for such children in West Nusa Tenggara, where each centre comprises 25 to 30 students. This means that 375 children in this province suffer from this mental health condition. Therefore, this experience requires many people to think about alternative therapies to help increase positive behaviour and reduce negative symptoms of children with autism. Experts and observers know several alternative therapies, but most have not been fully implemented. This is due to the limited facilities available in therapy centres hence no data and facts show evidence for the effectiveness of applying them to improve the abilities of this category of children. Based on these needs, this research aims to apply therapy with a